Produção de biohidrogenio (BioH2) a partir do processo fermentativo do soro de leite utilizando diferentes complexos bacterianos - Souza, André Luiz Viana (2018)
The development of societies, has always been interconnected energy sources, this way the H2 appears as a possible source. Nowadays, the biological pathway, the bacterial fermentation, has been highlighted, as it presents good productivity and low cost. The present work proposes to evaluate the potential of microbial consortia, which are easily accessible in the production of BioH2, by fermentation using the whey as a culture medium. This was done by productive complexes called PUBC (Pure Bacterial Complex), PIBC ( Pig Bacterial Complex), LACB (Land Bacterial Complex) and OXBC (Ox Bacterial Complex), where the fermentative medium was formed with 1ml of each complex and 6ml of culture medium, kept in a greenhouse with a temperature of 33ºC for a period of 07 days, where the concentration and production of the organic acids and gases were verified, resulting in 35% PUBC and 700 mLBioH2 / L (substrate) and with higher productivity of acetic acid, PIBC 36% and 1594 mLBioH2 / L, with higher concentration of butyric acid,LACB 37% and 1691 mLBioH2 / L, with higher productivity of succinic acid and OXBC 51% and 4371 mLBioH2 / L, with the productivity of organic acids divided into butyric and succinic. The results obtained showed a productive capacity of BioH2 and of organic acids, which in the case of OXBC obtained higher productive yield than works found in the current literature, making possible a new research and analysis to be done later.